Efficient reductive amination of HMF with well dispersed Pd nanoparticles immobilized in a porous MOF/polymer composite. Issue 2 (22nd November 2019) - Karve, Vikram V.; Sun, Daniel T.; Trukhina, Olga; Yang, Shuliang; Oveisi, Emad; Luterbacher, Jeremy; Queen, Wendy L.
Abstract : Making heterogeneous catalysis greener by improving nanoparticle stability in a MOF support modified with short polymeric chains. Abstract : Aminated derivatives of 5-hydroxymethylfurfural (HMF) and furfural are critical intermediates for the pharmaceutical industry. The state-of-the-art catalysts currently used for these syntheses are mostly homogeneous in nature, motivating the design of recyclable, heterogeneous catalytic systems. As such, the present study illustrates a new method for the design of metal–organic framework (MOF)/polymer composites containing well-defined metal nanoparticles in a sustainable way. One such palladium functionalized MOF/polymer composite is then employed in the reductive amination of HMF under mild conditions. The catalyst shows excellent activity, including a high TON/TOF (h −1 ) of 604.8/302.4 and ∼94% amine yield, which is maintained over a larger number of reaction cycles (up to 15) when compared to several state-of-the-art materials, such as a commercial Pd/C (3 cycles). It is thought that the origin of the improved catalyst recyclability is due to the added polymer, poly- para -phenylenediamine (P p PDA), which helps to prevent the aggregation and leaching of the palladium nanoparticles. The synthetic approach is further extended to design other potential catalysts with different metallic nanoparticles (NPs).